Rough modeling - A bottom-up approach to model construction - Loken, Terje; Komorowski, Jan (Zielona Góra: Uniwersytet Zielonogórski)
Traditional data mining methods based on rough set theory focus on extracting models which are good at classifying unseen objects. If one wants to uncover new knowledge from the data, the model must have a high descriptive quality - it must describe the data set in a clear and concise manner, without sacrificing classification performance.
Keywords: knowledge discovery; rough sets; rough modeling; descriptive models